2016
DOI: 10.1155/2016/8135135
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Saw Palmetto Supplements on Androgen‐Sensitive LNCaP Human Prostate Cancer Cell Number and Syrian Hamster Flank Organ Growth

Abstract: Saw palmetto supplements (SPS) are commonly consumed by men with prostate cancer. We investigated whether SPS fatty acids and phytosterols concentrations determine their growth-inhibitory action in androgen-sensitive LNCaP cells and hamster flank organs. High long-chain fatty acids-low phytosterols (HLLP) SPS ≥ 750 nM with testosterone significantly increased and ≥500 nM with dihydrotestosterone significantly decreased LNCaP cell number. High long-chain fatty acids-high phytosterols (HLHP) SPS ≥ 500 nM with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…SP extracts used extensively for treatment of LUTS in traditional medicine have been clinically validated for improving the conditions such as BPH [12]. These medicinal attributes of SP extracts are due to the synergistic effect of phytosterols and fatty acids [13]. Previously, we have demonstrated the improved efficacy of SP oil containing 3% β-sitosterol (VISPO) compared to the conventional oil in alleviating the symptoms of BPH in rats [11].…”
Section: Discussionmentioning
confidence: 99%
“…SP extracts used extensively for treatment of LUTS in traditional medicine have been clinically validated for improving the conditions such as BPH [12]. These medicinal attributes of SP extracts are due to the synergistic effect of phytosterols and fatty acids [13]. Previously, we have demonstrated the improved efficacy of SP oil containing 3% β-sitosterol (VISPO) compared to the conventional oil in alleviating the symptoms of BPH in rats [11].…”
Section: Discussionmentioning
confidence: 99%
“…This has been confirmed last month also in an obese mouse model [43] further paving the way to a wider systemic metabolic understanding of the disease [44][45][46][47]. In favour of such integrated phyto-pharmaceutic approach, it is worthwhile reporting that components such as specific pumking seed, red clover isoflavones, serenoa and pomegranate extracts have been shown to have antiandrogenic activity by dosedependently blocking the binding of DHT besides am anti-aromatase and anti-5-α-reductase Type II action [38,[48][49][50][51]. It goes without saying that inflammation per se exerts an endocrine disrupting effect at the prostate level by negatively affecting tissue estrogen metabolism [52], this being, together with antioxidant property, one of the suspected hormone receptor-independent anti-mutagenic mechanisms of some phytocompounds [53].…”
Section: Discussionmentioning
confidence: 89%
“…8,21,22 However, of note, many studies indicate that SPE may modulate androgen metabolism and/ or block the effects of androgens because of mitigation of androgen-induced increase in prostatic mass in castrated or non-castrated rodent models. 23,24 Wadsworth et al reported that in the prostate of transgenic adenocarcinoma of the mouse prostate model, treatment with 300 mg/kg/day SPE from 4 to 24 weeks of age significantly reduced the concentration of DHT in the prostate, supporting the view that inhibition of 5α-reductase is a mechanism of action of SPE. 22 Another trial performed by Governa et al validated that both sterols and fatty acids of SPE can play a role in the inhibition of 5α-reductase.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%